Developmental assets, creativity, thriving, and mental health among Malaysian emerging adults - Abdul Kadir, Nor Ba’yah; Rusyda, Helma Mohd (Frontiers in Psychology, 2022)
This study was part of a larger cross-national research project at the Norway’s University of Bergen, which involved participants from over 30 countries. This undertaking delves into developmental assets, creativity, and thriving, and the part they play in determining mental health. Thus, this study examined the developmental assets (internal assets: support, empowerment, boundaries, and expectations and creative use of time; external assets: commitment to learning, positive identity, positive values, and social competencies), creativity, thriving, and their importance to mental health in a sample of Malaysian emerging adults. This study was based on a sample of 394 undergraduate students, comprising 264 females and 130 males, ranging between the ages of 18 and 26 years (M = 21.5). Two subscales of the Reisman diagnostic creativity assessment (RDCA) were used to measure creativity (originality and fluency). Meanwhile, thriving indicators of Search Institute were used to measure thriving while the short form of the mental health continuum (MHC-SF) for adolescents was used to measure mental health. An online Google form was used to collect data from university students enrolled in both public and private universities. The correlation analysis results revealed that all the variables were positively correlated to each other and that the relationship between development assets, creativity, thriving, and mental health ranged from weak to moderate. Multiple regression (stepwise) analysis produced four models that indicated that positive identity, support, creativity, and thriving have a significant influence on mental health among emerging adults. Further, analyses using the PROCESS procedure demonstrated significant indirect effects of positive identity and support on mental health through its effects on creativity and thriving. As such, it is our recommendation that mental health practitioners tailor their treatment approach to include positive identity, support, creativity, and thriving in their sessions with Malaysian emerging adults.